The New Kid - English, Karen; Freeman, Laura (Illustrator) (Boston ; Clarion Books, 2017)
"Third-grader Gavin and his friends aren't sure what to make of the new boy in their class, Khufu. He doesn't look or act like other kids. When Gavin's bike goes missing, they think Khufu stole it, but did he?"--
Accelerated Reader AR
Keywords: JUVENILE FICTION / People & Places / United States / African American; JUVENILE FICTION / Social Issues / Friendship; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Social Issues / Bullying; JUVENILE FICTION / Social Issues / Peer Pressure; JUVENILE FICTION / Readers / Chapter Books